ZULLISONAINLIK ANANASINING HISTORICAL STARDS (TAMADDUN NURI JURNALI, 2026)
This thesis-article analyzes the historical roots of the zullisonayn tradition, the stages of its formation, its place in the culture of East and Central Asia, as well as the essence of this phenomenon on the example of famous zullisonayn artists.